2021
DOI: 10.1088/1757-899x/1037/1/012059
|View full text |Cite
|
Sign up to set email alerts
|

Global technology trends through patent data analysis

Abstract: The future success of companies directly depends on their innovative activity, research and development of newly technologies. The article examines global technological trends by comparing the number of patent applications in different fields and the degree of development of prominent business areas. These areas are also identified by the highest-ranking positions of the companies in the annual research of innovation in the world. The study highlights the most patentable technological fields, as well as those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This was due to the fact that within entrepreneurial universities, there is space for an effective dialogue between various educational, scientific, business and public authorities (Gogorishvili and Zarandia, 2021;Seturidze and Topuria, 2021; Vesperi and Gagnidze, 2021b). Moreover, these authorities can quickly commercialise research, introduce the results to the market, and retrain fully qualified specialists (Guerrero et al, 2016;Kharadze et al, 2021;Lekashvili and Bitsadze, 2021;Papachashvili et al, 2021;Sciarelli et al, 2022;Sobolieva et al, 2021). Due to their relevance, below a few key factors have been identified that contribute to the efficient functioning of entrepreneurial universities, namely: the creation of an "entrepreneurial environment, entrepreneurial staff as well as entrepreneurial teaching and learning; a strong entrepreneurial vision and the presence of leaders; the need for an environment of awareness to support spin-off creation; identifying factors that determine continuous organisational success" (Dominici and Gagnidze, 2021, p. 24).…”
Section: What Characteristics Will Enable the Cluster To Overcome The...mentioning
confidence: 99%
See 1 more Smart Citation
“…This was due to the fact that within entrepreneurial universities, there is space for an effective dialogue between various educational, scientific, business and public authorities (Gogorishvili and Zarandia, 2021;Seturidze and Topuria, 2021; Vesperi and Gagnidze, 2021b). Moreover, these authorities can quickly commercialise research, introduce the results to the market, and retrain fully qualified specialists (Guerrero et al, 2016;Kharadze et al, 2021;Lekashvili and Bitsadze, 2021;Papachashvili et al, 2021;Sciarelli et al, 2022;Sobolieva et al, 2021). Due to their relevance, below a few key factors have been identified that contribute to the efficient functioning of entrepreneurial universities, namely: the creation of an "entrepreneurial environment, entrepreneurial staff as well as entrepreneurial teaching and learning; a strong entrepreneurial vision and the presence of leaders; the need for an environment of awareness to support spin-off creation; identifying factors that determine continuous organisational success" (Dominici and Gagnidze, 2021, p. 24).…”
Section: What Characteristics Will Enable the Cluster To Overcome The...mentioning
confidence: 99%
“…, 2021; Lekashvili and Bitsadze, 2021; Papachashvili et al., 2021; Sciarelli et al. , 2022; Sobolieva et al. , 2021).…”
Section: What Characteristics Will Enable the Cluster To Overcome The...mentioning
confidence: 99%